Pengaruh Likuiditas, Profitabilitas, dan Solvabilitas terhadap Harga Saham (Studi Empiris pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019–2022) - Aidia, Ariqah (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of liquidity, profitability, and solvency on stock prices in food and beverage companies listed on the Indonesia Stock Exchange during the 2019–2022 period. The study employs a quantitative approach using secondary data obtained from annual reports and stock-market information. The sample was selected through purposive sampling and initially consisted of 20 companies with 80 firm-year observations. After data screening, 64 observations were included in the analysis. Liquidity was measured using the Current Ratio, profitability was measured using Return on Equity, and solvency was measured using the Debt-to-Equity Ratio. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with IBM SPSS version 26. The results show that liquidity and solvency have no significant effects on stock prices, while profitability has a positive and significant effect. Simultaneously, liquidity, profitability, and solvency significantly affect stock prices. The coefficient of determination is 47.9%, indicating that the three independent variables explain 47.9% of the variation in stock prices.